Polarization microscopic tomography of the polycrystalline structure of vitreous body preparations in diagnostics time of the since death - Sarkisova, Yu. V.; Bachynskyy, V. T.; Ushenko, O. H.; Melnyk, M. M. (Modern medical technology, 2019)
Purpose of the study. Develop a complex of new forensic objective criteria to enhance the functionality of accurate definition time of the since death (TSD) estimation according to polarization microscopic tomography of the polycrystalline structure of human vitreous body (VB). Materials and methods. The object of study is polycrystalline VB layers taken from 56 people who died from cardiovascular disease with known time of death ranged from 3 to 36 h. Measuring parameter distributions of birefringence of the polycrystalline component of VB preparations were carried out with a standard Stokes-polarimeter. Results. The time dynamics of the magnitude of the set of statistical moments of the 1–4th order, which characterize the distributions of the birefringence of the polycrystalline component of the VB layers at different TSD values were investigated. The sensitivity range of the method of polarization tomography of the distributions of the birefringence of the polycrystalline component of the VB layers was determined (24 h), with the accuracy of TSD estimation – 20 min. The efficiency of wavelet analysis of the distribution of the magnitude of the birefringence layers of human VB layers at different TSD values is demonstrated. Scale-selective analysis has been shown to increase the sensitivity range up to 36 h while increasing the accuracy of TSD determination to 15 min. Conclusion. The efficiency of the method of polarization microscopic tomography of the polycrystalline structure of human VB preparations in the determination of TSD is demonstrated. Sensitivity ranges method up to 36 h was determined with an accuracy of up to 15 min.